Demythologization of Mythological Women as Upliers of Food Security Systems In Indonesian Literature Based on Cultural Folk Stories - Mulyono Mulyono; Dyah Prabaningrum; Kushardiyanti Novinda; Dwi Puspitosari; Siska Rakhmawati (UIN Raden Mas Said Surakarta, Indonesia, 2026)
Food security is generally understood as a matter of economics, technology, and public policy. However, cultural and literary values ​​also play a significant role in building public awareness of food sustainability. Nusantara folktales feature mythological female figures who symbolize fertility, sustainability, and natural resource management, yet these meanings have not been widely studied in the context of modern Indonesian literature. This study aims to construct the meaning of mythological women as upholders of the food security system by reading modern Indonesian literary texts derived from the folklore of Dewi Sri, Dewi Sinta, and Ratu Kidul. The study used a qualitative approach with a dialectical hermeneutic method and a demythologization perspective. Data were collected in the form of words, phrases, sentences, and narratives representing mythological women in modern Indonesian poetry, prose, and drama. Analysis was conducted through heuristic reading, hermeneutic interpretation, and the construction of contextual meaning. The results show that Dewi Sri symbolizes food production and sustainability, and Dewi Sinta symbolizes moral resilience and sustainability. In contrast, Ratu Kidul and Nawang Wulan represent resource management and harmony between humans, nature, and spirituality. These findings show that modern Indonesian literature not only reproduces traditional myths but also transforms them into cultural discourses relevant to contemporary food security issues. Ketahanan pangan umumnya dipahami sebagai persoalan ekonomi, teknologi, dan kebijakan publik, padahal nilai-nilai budaya dan sastra juga memiliki kontribusi penting dalam membangun kesadaran masyarakat mengenai keberlanjutan pangan. Berbagai cerita rakyat Nusantara menghadirkan figur perempuan mitologis yang berperan sebagai simbol kesuburan, keberlanjutan hidup, dan pengelolaan sumber daya alam, namun makna tersebut belum banyak dikaji dalam konteks sastra Indonesia modern. Penelitian ini bertujuan mengonstruksi makna perempuan mitologis sebagai penegak sistem ketahanan pangan melalui pembacaan terhadap teks sastra Indonesia modern yang bertransformasi dari folklor Dewi Sri, Dewi Sinta, dan Ratu Kidul. Penelitian menggunakan pendekatan kualitatif dengan metode hermeneutika dialektis dan perspektif demitologisasi. Data berupa kata, frasa, kalimat, dan narasi yang merepresentasikan perempuan mitologis dalam puisi, prosa, dan drama Indonesia modern. Analisis dilakukan melalui pembacaan heuristik, interpretasi hermeneutik, dan konstruksi makna kontekstual. Hasil penelitian menunjukkan bahwa Dewi Sri merepresentasikan simbol produksi dan keberlanjutan pangan, Dewi Sinta merepresentasikan ketahanan moral dan keberlanjutan hidup, sedangkan Ratu Kidul dan Nawang Wulan merepresentasikan pengelolaan sumber daya serta harmoni antara manusia, alam, dan spiritualitas. Temuan ini menunjukkan bahwa sastra Indonesia modern tidak hanya mereproduksi mitos tradisional, tetapi juga mentransformasikannya menjadi wacana budaya yang relevan dengan isu ketahanan pangan kontemporer.